Cholestasis in Chronic Liver Disease and the Role of Ademetionine in its Treatment (Literature Review and Expert Panel Resolution) - K. L. Raikhelson; A. O. Bueverov; E. A. Kondrashina; M. V. Maevskaya; I. B. Khlynov; E. N. Shirokova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: to analyse the principles of diagnosis and treatment of intrahepatic cholestasis in chronic liver diseases, to present data on the effectiveness of ademetionine in the treatment of chronic liver diseases with intrahepatic cholestasis and the materials of the Expert Meeting held in 2023.   Key points. During the Expert Meeting, the problems of diagnostics and treatment of intrahepatic cholestasis in various chronic liver diseases were discussed, the effectiveness of ademetionine was clarified, and optimal regimens for its administration were determined. The relevance of the existing algorithm for diagnosing cholestasis in real clinical practice was assessed. The effectiveness of ademetionine in the treatment of various liver diseases occurring with intrahepatic cholestasis (cholestatic forms of drug-induced liver damage, alcoholic liver disease, non-alcoholic liver disease, primary biliary cholangitis) was demonstrated, manifested by a decrease in clinical and laboratory signs of cholestasis. The anticholestatic mechanisms of ademetionine action were clarified, which consist in normalizing the fluidity of hepatocyte membranes, regulating the activity of Nrf2, a key transcription factor, suppressing lipid peroxidation and the resulting damage to hepatocytes and cholangiocytes. Optimal regimens for prescribing ademetionine for various clinical situations were considered.   Conclusions. Ademetionine is an effective drug that, due to its pleiotropic action and favourable safety profile, can be used in various chronic liver diseases accompanied by cholestasis, including as a part of the complex therapy.